Geology and geoheritage of Bukit Marak, Bachok, Kelantan. - Muhamad Alif Ramli (2017)
Geological heritage or also known as geoheritage is one of the subdiscipline in geology. It focuses on the developing and conserving geological sites that have the geoheritage values. Sites that have numbers of unique geological features such as karst landform, granite hills and rivers are conserved and developed for future generation. The objectives of the study are clear as to produce an updated geological map and to identify the geoheritage and geotourism potential of the study area. The study area was maped as it has an outdated geological data. Bachok is mainly known for the groundwater aquifer in terms of geology. But, some places in Bachok such as Bukit Marak can be a good geoheritage sites as it possesses so many geological features that can linked up with geoheritage values and able to attract visitors. In order to recognize any geoheritage sites, there are several systematic steps which are inventory, characterization, classification, assessment, and evaluation of potential geoheritage resources in the study area. These methods were used to verify whether Bukit Marak can be a good geoheritage site or not. The analysis is clear that the study area can be a good potential of geotourism and need to be conserved and developed for the visitors.